Modified model for end-stage liver disease score predicts 30-day mortality in high-risk patients with acute pulmonary embolism admitted to intensive care units. (30th July 2021) - İdin, Kadir and Dereli, Seçkin and Kaya, Ahmet and Yenerçağ, Mustafa and Yılmaz, Ahmet Seyda and Tayfur, Kaptanıderya and Gülcü, Oktay
Abstract: Objectives: The Model for End-stage Liver Disease excluding the international normalised ratio that is derived from prothrombin time which is calculated as a ratio of the patient's prothrombin time to a control prothrombin time standardized (MELD-XI) and modified MELD, which uses albumin in place of the international normalised ratio (MELD-Albumin) scores reflect liver and renal function and are predictors of mortality. However, their prognostic value in acute pulmonary embolism (APE) has not been studied. Design: We assessed the predictive value of the MELD scores in patients diagnosed with high-risk APE admitted to the intensive care unit. The primary outcome was 30-day mortality. Results: Of the 273 patients included in the study, 231 were survivors and 42 were non-survivors. The mortality rate was 15.3%. The mean MELD-XI and MELD-Albumin scores were significantly higher in the non-survivors than in the survivors (MELD XI, 11.8 ± 1.8 and 10.6 ± 1.43, respectively; p = .002; MELD-Albumin, 10.5 ± 1.6 and 8.7 ± 1.1, respectively; p = .001). The multiple logistic regression analysis identified the MELD-XI (hazard ratio: 3.029, confidence interval: 1.06–1.21, p = .007) and MELD-Albumin (hazard ratio: 1.13, confidence interval: 1.06–1.21, p = .002) scores as independent predictors of mortality. Receiver operating characteristic analysis revealed that the predictive power of the MELD-Albumin score (0.871 ± 0.014; p < .001) was higher than those of the MELD-XI (0.726 ± 0.022, p < .001), APACHE III (0.682 ± 0.024, p < .001), and PESI (0.624 ± 0.023, p < .001) scores. Conclusions: The MELD-Albumin score is an easily calculable, reliable, and practical risk assessment tool and independent predictor of 30-day mortality in patients with high-risk APE.